Odporne metody estymacji współczynnika Beta na przykładzie polskiego rynku akcji - Kaszuba, Bartosz (Robust Measurement of Beta Risk, 2008)
Many empirical studies find that the distribution of stock returns departs from normality. In such cases, it is desirable to employ a statistical estimation procedure that may be more efficient than ordinary least squares (OLS). The main goal of this article is compare OLS estimation with various robust methods in the context of estimating beta risk. This article studies the stability of the beta risks in single index Sharp's model, calculated using robust methods and OLS estimation. The stability of the beta risks was examined for 7 companies included in the WIG20 index, basing on Stock Exchange quotations since 1997-07-01. Futhermore, this paper describes and compares various estimators of the parameters of linear regression models. This article describe least absolute values methods, Huber M-estimation, bisquare M-estimation, least median of squares and least trimmed mean estimation.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 18, s. 38-48